Peranan Parpol dalam Pendidikan Politik dan Wawasan Kebangsaan - MUHAMMAD ARIFIN NASUTION (Politeia: Jurnal Ilmu Politik, 2012)
This study describes the role of political parties to develop the concept of wawasan kebangsaan in Indonesia. This role relates to the law on political parties (Undang-Undang Partai Politik No. 31 Tahun 2003). In this law there are rules about political education for the community. The study found that the role of political parties is strategic to promote the concept of wawasan kebangsaan. But unfortunately there is a gap between planning and implementation of educa-tional insight in terms of wawasan kebangsaan and party themes. There are several factors that cause the condition. First, the political parties does not have large financial resources. Second, existing human resources have less political awareness. Third, political parties are concerned with power. The divergence of interests between the political parties (as the political institu-tions) and government (as the holder of power), impact on congestion of the program for strengthening the concept of wawasan kebangsaan. This study supported by data sourced from library and documents and using institutional and political system approach in analysis procces.Keywords: Political education, political parties, nationalism, wawasan kebangasaan.